Research of The Possibilities of Reducing the Quantity of CO2 in the Premises of the E&E Foundry in Gjakova - Bajraktari Gashi, Zarife; Ibrahimi, Izet (International Journal of Computational and Experimental Science and Engineering, 2025)
The cupola furnace is a type of melting furnace used in foundries for melting cast iron. The primary purpose of studying the emission of gases in the cupola furnace is to understand and mitigate environmental and operational impacts. Emission research in the cupola furnace involves the analysis of gases released during the melting process. The key gases of interest include carbon dioxide (CO2), carbon monoxide (CO), sulfur dioxide (SO2), and nitrogen oxides (NOx). Environmental Impact: Understanding the composition and quantity of emissions helps in assessing the environmental impact of cupola furnace operations. This is crucial for compliance with environmental regulations and standards. Studying gas emissions provides insights into the combustion efficiency and overall performance of the cupola furnace. It allows for optimization of the process to enhance energy efficiency and reduce emissions. Worker Health and Safety: Monitoring emissions is essential to ensure a safe working environment for foundry workers. At Foundry E&E, a total of 7800 kg of pig iron is produced during one scrap smelting. Measurements of process gases in the working spaces and in the chimney exceed the standard values of CO2 and CO quantities. We performed the measurements with the "aeroqual-gas sensing" series 500 apparatus. The amount of CO2 near the scarp melting cupola furnace was 325 ppm, while the amount of CO2 in the chimney reached the value of 2047 ppm. The aim of the work is to achieve the reduction of metallurgical coke, and the return of the process gas through the blowers in the areas of the cupola furnace in the Foundry E&E, and with this we will achieve the reduction of CO2